Food inflation and food price volatility in India: Trends and determinants - Sekhar, C. S. C.; Roy, Devesh; Bhatt, Yogesh (International Food Policy Research Institute, 2017)
The study analyzes food inflation trends in India over the last decade. Annual trends show that different commodities have contributed to food inflation in different years and that no single commodity shows uniformly high inflation. A decomposition exercise shows that eggs, meat, fish, milk, cereals, and vegetables were generally the main contributors to recent food inflation. The contribution of pulses, except pigeon peas (arhar), and of edible oils remained low. Fruits and vegetables displayed a much higher degree of intrayear volatility, and high-weight commodities in the national consumption basket also showed very high inflation rates, which is a cause for concern. Results of the econometric analysis show that both supply and demand factors are important. Cereal and edible oil prices appear to be mainly driven by supply-side factors such as production, wage rates, and minimum support prices. For pulses, the effects of supply- and demand-side factors appear almost equal. The prices of eggs, meat, fish, milk, and fruits and vegetables appear to be driven mainly by demand-side factors.